CHALLENGES AND PROSPECTS FOR THE IMPLEMENTATION OF THE PROTOCOL UNDER ENHANCED RECOVERY TO THE COLON CANCER - A. M. Karsanov; S. S. Maskin; I. N. Klimovich; Z. O. Karsanova (Медицинский вестник Юга России, 2016)
Objective: examine the possibility of introducing enhanced recovery protocol (ERP) in the surgical treatment of colon cancer. Materials and methods: the article on the model of treatment of 77 patients studied the possibility of introducing ERP after surgery for colon cancer. In the study group (35 patients) was used to adapt to the particular branch of option ERP. In 42 patients of the control group it was used traditional methods of perioperative management. Results: in the structure of postoperative complications in the study group was dominated by the system, then in the comparison group prevailed as severe intra-abdominal excesses and Extra-serious complications. In the study group had achieved a threefold reduction in the incidence of general complications (17% vs. 45%) and reduction in the duration of the postoperative period, from 13 to 9,1 days in case that the average frequency reproducibility ERP components was 83,7%. Conclusions: the introduction of a local ERP significantly reduces is a common frequency and severity of post-operative complications.